Brief, pragmatic measure of emotion dysregulation in young people – a preliminary validation of the BER-5 - Iselin Solerød Dibaj; Sudan Prasad Neupane; Lars Mehlum (Borderline Personality Disorder and Emotion Dysregulation)
Abstract Background Emotion dysregulation is a transdiagnostic construct associated with mental health problems, including self-harm and borderline personality disorder (BPD). Although often targeted in clinical practice, the majority of psychometric assessment instruments of emotion dysregulation are developed for research purposes, and there is a need for an adapted version to be used in a clinical screening setting. The main aim of this study was to examine psychometric properties of a brief, pragmatic measure of emotion dysregulation, the Brief Emotion Regulation Scale − 5 items (BER-5). Methods The sample consisted of 60 young adults (mean age 28.1 years) who participated in a 12.4 years follow-up study of an RCT of Dialectical Behaviour Therapy’s long-term effect. Cronbach’s alpha was used to calculate internal consistency. Concurrent and convergent validity were examined using Spearman’s correlation in comparison with other measures, and logistic regression as well as area under the curve to examine its ability in terms of differentiating between BPD diagnosis and trait levels. Optimal cut-off points were explored using Receiver Operating Curves. Results Our results indicated adequate internal consistency both in adolescence and in young adulthood, as well as high convergence with a gold-standard measure of emotion dysregulation, and moderate convergence with symptom measures of anxiety and depression. BER-5 was able to differentiate between participants with no BPD from subthreshold or full BPD diagnosis in adulthood, and a cut-off score of 5 was found optimal in terms of sensitivity and specificity in identifying individuals with BPD. Conclusions The BER-5 is a brief, pragmatic measure of emotion dysregulation with good psychometric properties and is potentially a useful screening tool for clinicians working in specialized health care settings.